Evaluating the implementation of the Inverse Care Law Programme in Wales, a population based intervention in primary care - Akbari, Ashley; Song, Jiao; Cox, Caryn; May, Leon; Watkins, Williams; Thomas, Sarah; Aitken, Sarah; King, William (International Journal of Population Data Science, 2018)
Introduction The Inverse Care Law (ICL) programme in Wales was setup to identify people in deprived communities at risk of cardiovascular disease (CVD) through a health check; offering lifestyle and medical intervention as appropriate. Evaluation of this programme to tackle health inequalities ensuring services are available is vital. Objectives and Approach To evaluate the uptake and long term outcomes of the programme, using longitudinal evidence-based results, it was necessary to develop an efficient and cost effective approach with a readily available source of data. To achieve this, the Welsh Longitudinal General Practice (WLGP) data held in Secure Anonymised Information Linkage (SAIL) databank was utilised, with programme-specific code deployed within primary care at the point of the health check, which identified the intervention, potential CVD risks, referrals and any follow-up. Lifestyle risk factors could be evaluated such as poor diet, physical inactivity, smoking and high alcohol intake. Results Utilising routine data sources and reproducible SQL (Standard Query Language), we evaluated the programme initialisation between February 2015 and November 2016, and found of 55 General Practices who participated, 31 of 35 in Aneurin Bevan (AB) and 17 of 20 in Cwm Taf (CT) University Health Boards, providing data which allowed identification of the health check and associated outcomes of interest in the routine data, with 3 (2 AB, 1 CT) since delivering. There are ongoing evaluations on the various risk factors longitudinally as well as the overall implementation of the programme itself, with this collaborative approach succeeding in utilising existing powerful data linkage within the SAIL databank to identify our intervention and facilitate long-term follow-up at an individual level using robust information governance mechanisms. Conclusion/Implications Lessons learned and challenges encountered are being fed back as part of our evaluation, with further work assessing the long term population level outcomes and impact of the health check and services provided across these deprivation groups, informing and refining programme delivery of similar work across Wales in the future.